1997
DOI: 10.1021/bi971306u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Minor Conformer of a DNA Duplex Containing a dG Mismatch Opposite a Benzo[a]pyrene Diol Epoxide/dA Adduct:  Glycosidic Rotation from Syn to Anti at the Modified Deoxyadenosine

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants whose metabolism in mammals results in deleterious cell transformation. Covalent modification of DNA by diol epoxides metabolically formed from PAHs such a benzo[a]pyrene (BaP) provides a mechanism for the genotoxicity, mutagenicity, and carcinogenicity of PAHs. We had previously reported NMR evidence for a minor conformer of the duplex d(G1G2T3C4A5*C6G7A8G9).d(C10T11C12G13G14G15A16C17C18) containing a dG14 mismatch opposite a dA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(105 citation statements)
references
References 18 publications
6
99
0
Order By: Relevance
“…20,21 The 10R(Ϫ)-trans-anti adduct structure shown is essentially the same as that of the NMR solution structure of Zegar et al 22 determined in the same C[A*]A sequence context of codon 61 of the human N-ras gene.…”
Section: Adduct Structuressupporting
confidence: 58%
See 3 more Smart Citations
“…20,21 The 10R(Ϫ)-trans-anti adduct structure shown is essentially the same as that of the NMR solution structure of Zegar et al 22 determined in the same C[A*]A sequence context of codon 61 of the human N-ras gene.…”
Section: Adduct Structuressupporting
confidence: 58%
“…NMR solution structures provided starting models for these simulations. 16,17,21,22 gives rise to multiple and poorly resolved NMR resonances, as well as line broadening, all of which preclude a determination of a high-resolution structure for this stereoisomeric adduct. 21,[23][24][25] However, when the T complementary to the 10S(ϩ)-trans-anti-B[a]P-N 6 -dA is replaced by a mismatched G two different conformations were discerned and characterized.…”
Section: S(ϩ) Trans-anti-b[a]p-nmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the stability of a (ϩ)-anti-trans-BPDE-adducted adenine mismatched with dG is significantly higher than the stability of the adducted adenine paired with the correct dT (41,43). This suggests that the differences in stability between the incorrect and correct base pairs containing the different diastereomers may play a role in BPDEinduced mutagenesis.…”
Section: Discussionmentioning
confidence: 99%